Effects of landscape modification on species richness patterns of fruit‐feeding butterflies in Brazilian Atlantic Forest. Issue 2 (19th November 2019) - Santos, Jessie P.; Sobral‐Souza, Thadeu; Brown, Keith S.; Vancine, Maurício Humberto; Ribeiro, Milton C.; Freitas, André V. L.
Abstract: Aim: To assess the distributional patterns of fruit‐feeding butterfly species richness in Atlantic Forest (AF) based on stack species distribution models (SSDM); to evaluate the relative contribution of climate and landscape in the patterns of butterfly species richness; and to recommend conservation guidelines for AF regions based on the obtained results. Location: Brazilian Atlantic Forest. Methods: We used SSDMs to generate potential distribution maps of butterfly species richness in AF. Our dataset comprises 7, 062 records of 279 species, distributed across 122 local communities. We built richness maps based on climate and landscape models and analysed them separately to understand their contribution to the pattern of richness distribution. Then, we combined both models to build a consensus map. Finally, we designed specific conservation strategies based on richness categories distributed on the consensus map. Results: The regions with high‐predicted species richness for both climate and landscape models supported the main endemism locations described for other AF taxa in previous studies. Both models predicted intermediate values of species richness for most regions, but the patterns of richness distribution were not fully congruent. High species richness based on landscape metrics was frequently concentrated in the south. Furthermore, locations suitable for high species richness according to climate are near to the endemism centres, but also to dense urban centres, highlighting the potential impacts of the landscape modification on butterfly species richness. Main conclusions: The distribution of fruit‐feeding butterfly species richness and endemism reflect the classic division of AF in different sub‐regions according to the endemism centres proposed by previous authors for other taxa. The availability of forested habitats seems to be a determining factor for the maintenance of high species richness in AF. Therefore, the loss of natural forest remnants due to landscape modification is the primary threat to butterfly diversity.